It hurts (stock prices) when your team is about to lose a soccer match - Michael Ehrmann; David-Jan Jansen (Bank of Canada, 2014)
The end result of major sporting events has been shown to affect next-day stock returns through shifts in investor mood. By studying the soccer matches that led to the elimination of France and Italy from the 2010 FIFA World Cup, we show that moodrelated pricing effects can materialize as sporting events unfold. We do this by using intraday stock prices for a firm cross-listed on the Paris and Milan stock exchanges. This strategy allows for a straightforward identification of pricing effects. During the soccer matches, stock prices in the country that eventually loses are lower by up to seven basis points. The probability of underpricing increases as elimination from the tournament becomes more likely.
Keywords: G02; G12; G14; G15; 330; Asset pricing; Financial markets